PENERAPAN MEDIA STIKER HURUF UNTUK MENINGKATKAN KEMAMPUAN KEAKSARAAN ANAK USIA 4-5 TAHUN - Farida, Ida; Cecep, Cecep; Fatah, Abdul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Early childhood literacy skills are an important foundation for literacy development and academic readiness. However, many children aged 4–5 years still have difficulty recognizing letters and initial sounds of words due to monotonous learning and minimal use of concrete media. This study aims to determine the effectiveness of letter sticker media in improving early childhood literacy skills at Nurul Hikmah PAUD. The study was conducted using the Classroom Action Research (CAR) method in two cycles, including planning, implementation, observation, and reflection. The research subjects were 16 children aged 4–5 years. The results showed a significant increase in children's literacy skills, from an average of 39% in the pre-cycle with a dominance of the Not Yet Developing (BB) and Starting to Develop (MB) categories, increasing to 58% in the first cycle with more children entering the Developing According to Expectations (BSH) category, to reaching 82% in the second cycle with the majority of children in the BSH and Very Well Developing (BSB) categories. These findings prove that letter sticker media can be an effective, enjoyable, and developmentally appropriate learning strategy for early childhood. In conclusion, this study shows that letter sticker media can be an effective, fun learning strategy, and is appropriate to the developmental stages of early childhood, so it is worthy of being adopted in PAUD education practices.